2006
DOI: 10.1111/j.1572-0241.2006.00588.x
|View full text |Cite
|
Sign up to set email alerts
|

Coagulopathy Does Not Fully Protect Hospitalized Cirrhosis Patients from Peripheral Venous Thromboembolism

Abstract: Approximately 0.5% of admissions involving cirrhosis patients resulted in a new thromboembolic event. Low serum albumin was strongly predictive of increased risk for developing VTE, independent of international normalized ratio or platelet count. Serum albumin deficiency may indicate low levels of endogenous anticoagulants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
308
5
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(342 citation statements)
references
References 21 publications
21
308
5
8
Order By: Relevance
“…Venous thromboembolism is considered a very rare event in patients with liver cirrhosis, with unpredictable course and unclear mechanism. When comparing our results with the report by Northup et al [6], we found that the incidence of DVT was higher in our series. This discrepancy might be due to different characteristics of our study populations.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Venous thromboembolism is considered a very rare event in patients with liver cirrhosis, with unpredictable course and unclear mechanism. When comparing our results with the report by Northup et al [6], we found that the incidence of DVT was higher in our series. This discrepancy might be due to different characteristics of our study populations.…”
Section: Discussionsupporting
confidence: 77%
“…The first study on hypercoagulation in cirrhotic patients reported that approximately 0.5% of all admissions resulted in a new diagnosis of a VTE event, which consisted of 65.5% DVT, 19.5% pulmonary embolism (PE), and 15% both [6]. The mechanisms of thrombosis are not clear and no other report has studied this phenomenon in more detail.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with cirrhosis VTE may occur either in portal or peripheral veins [42,43]. When VTE occurs, the use of anti-coagulants (heparins and VKA) becomes an option.…”
Section: Monitoring Anti-thrombotic Therapymentioning
confidence: 99%
“…Estimates of VTE in patients with cirrhosis are discordant [42,43,[166][167][168][169][170][171][172][173][174][175][176], due to retrospective collection of data, high heterogeneity of patients' characteristics, and study design. Reported rates range from 0.5% to 6.7% for incidence (Table 2), and from 0.6% to 4.7% for prevalence (Table 3), with higher values in patients with more severe liver disease [173] and in those with hepatocellular carcinoma [176].…”
Section: Venous Thromboembolism In Liver Cirrhosismentioning
confidence: 99%
“…Lowering or normalizing INR values in patients with bleeding events, such as variceal bleeding, does not lead to improved outcomes or decreased failure rates in hemorrhage control [15]. Additionally, a study by Ewe found that INR was not predictive of liver bleeding time after laparoscopic liver biopsy [16]. …”
Section: Discussionmentioning
confidence: 99%